The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1977
DOI: 10.1161/01.cir.56.2.199
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of angiographic estimates of myocardial infarct size and accumulated release of creatine kinase MB isoenzyme in man.

Abstract: Accumulated creatine kinase MB isoenzyme release (sigma CK-MB) during acute myocardial infarction was correlated with biplane left ventricular (LV) angiographic estimates of percent abnormally contracting segment (%ACS) and ejection fraction (EF) in 35 patients who underwent diagnostic angiography at a mean of 33 +/- 4 days post myocardial infarction (MI). Of the 35 patients, 18 had no evidence of prior MI and their sigma CK-MB showed good correlation with %ACS (r = 0.84) and with EF (r = - 0.78). An additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(33 citation statements)
references
References 36 publications
5
28
0
Order By: Relevance
“…The maximum concentration of CK-MB is related to the grade of myocardial damage, [23][24][25][26] and the present study showed a close relationship between the maximum concentrations of M and CK-MB. The study data suggested that the maximum concentration of M, which was obtained at 6-12 h after onset, could be related to the grade of myocardial damage.…”
Section: Relationship Between Maximum Concentrations Of Serum Myoglobsupporting
confidence: 78%
“…The maximum concentration of CK-MB is related to the grade of myocardial damage, [23][24][25][26] and the present study showed a close relationship between the maximum concentrations of M and CK-MB. The study data suggested that the maximum concentration of M, which was obtained at 6-12 h after onset, could be related to the grade of myocardial damage.…”
Section: Relationship Between Maximum Concentrations Of Serum Myoglobsupporting
confidence: 78%
“…Although the accumulated release of CK and CK-MB is more accurate for estimating infarct size than peak CK and CK-MB levels, 35 we were restrained from using the former because of the lack of some measurement data after 24 h. Although large epidemiological studies have extensively used M-mode echocardiography, technical limitations exist when calculating LVM in patients with myocardial infarction, particularly in those who have a regional wall motion abnormality. However, several studies have demonstrated a strong relationship between LV hypertrophy detected by echocardiography and necropsy.…”
Section: Study Limitationsmentioning
confidence: 99%
“…The SEE is about 25%, which, on average, gives a 95% confidence limit of ± 50% for the individual IS. Studies in man concerning the accuracy of estimating IS by serum CK and CK-MB measurements have shown a good correlation between accumulated serum CK and CK-MB and different indirect expressions of IS.10, [16][17][18] Whether the kinetics of CK-MB should be described as a one-or multicompartment model has been discussed. The onecompartment theory is supported by a monoexponential elimination of labeled CK in experimental dog studies,9' 29 but this is probably a simplification of a complex biologic system.…”
Section: Content Of Ck-mb In Normal Myocardiummentioning
confidence: 99%
“…Recent studies comparing IS estimated from serum CK-MB with indirect indicators indicate that this is the case. [16][17][18] We demonstrated that the IS can be calculated just as well with only few blood samples as with serial samples,"' allowing us to examine the reliability of en-…”
mentioning
confidence: 99%